2014
DOI: 10.1080/13674676.2014.950558
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating and self-objectification in college women: clarifying the roles of spirituality and purpose in life

Abstract: Spirituality and purpose in life have been associated with positive mental health outcomes. This study examined the effects of spirituality, religiousness, and purpose in life on self-objectification and disordered eating. An ethnically diverse sample of college women (N = 161), aged 18-25, who were enrolled in the undergraduate level psychology courses, participated by completing a survey assessing relational spirituality, intrinsic religiousness, and purpose in life, as well as self-objectification and disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Individuals also felt vulnerable in church settings that did not understand their condition. Our findings highlighted how social media could be positive, including access to religious communities whilst avoiding unhelpful social media use, but self-objectification in relation to social media use did impact participant’s eating disorders (Cottingham, 2014 ). Intrinsic religiousness also buffered against this impact and resulted in less body image dissatisfaction (Homan & Cavanaugh, 2013 ).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Individuals also felt vulnerable in church settings that did not understand their condition. Our findings highlighted how social media could be positive, including access to religious communities whilst avoiding unhelpful social media use, but self-objectification in relation to social media use did impact participant’s eating disorders (Cottingham, 2014 ). Intrinsic religiousness also buffered against this impact and resulted in less body image dissatisfaction (Homan & Cavanaugh, 2013 ).…”
Section: Discussionmentioning
confidence: 77%
“…Much of the research on religion and eating disorders has been predominantly quantitative (Exline et al, 2016 ; Forthun et al, 2003 ; Geller et al, 2018 ; Goulet et al, 2017 ; Smith et al, 2004 ; Strenger et al, 2016 ) and much research has been conducted in the US. These studies often draw on undergraduates particularly from private American Christian colleges (See Homan & Boyatzis, 2010 ; Homan & Cavanaugh, 2013 ; Cottingham et al, 2014 ) or with patients from eating disorder clinics (see Richards et al, 2007 ) as in-patients (Malson et al, 2011 ). Findings from these studies reveal both the “positive and negative associations with disordered eating and psychopathology” (Akrawi et al, 2015 :4) focusing on attachment to God (Strenger et al, 2016 ) and divine struggles in relation to eating disorders (Exline et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that the relation between self-objectification and eating behaviors was mediated by body image concerns (Calogero & Pina, 2011; Tiggemann & Slater, 2015). Furthermore, two other studies explored spiritual conditions that modulated the association between self-objectification and disordered eating behavior (Cottingham, Davis, Craycraft, Keiper, & Abernethy, 2014); Liss & Erchull, 2015), revealing that this association was buffered by higher levels of self-compassion (Liss & Erchull, 2015) but not spirituality/religiousness (Cottingham et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The link between these aging concerns and scores on EDI-3 scales that indicate personal and interpersonal ineffectiveness, along with personal alienation in particular, also suggest this and confirm research findings that DE amongst female university students associates with greater interpersonal problems ( Stapleton & Empson, 2013 ) and alienation ( Power & Lazenbatt, 2015 ). Those with less purpose in life also report more DE ( Cottingham, Davis, Craycraft, Keiper, & Abernethy, 2014 ). Similarly, different life dissatisfactions relate to specific DE behaviors in this group ( Lucette, 2012 ; Matthews, 2009 ; Matthews et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%